Implementation Of Agricultural Technology at PT. Buyung Putra Perkasa in Pemulutan Sub-District District Ogan Ilir South Sumatera - Franchika, Tri Mulia; Waliyah, Siti; Ramkita, Milsani; Febrianti, Rika (International Journal of Community Service & Engagement, 2025)
The majority of the population in Indonesia lives in rural areas; agriculture is the primary sector in the economy, and the survival of rural communities. The development of the use of agricultural technology is needed to improve the quality and quantity of production, along with advances in science and technology, to meet food as one of the basic needs of human life—the application of agricultural technology in both pre-harvest and post-harvest activities. Agricultural technology aims to increase labor productivity, increase land productivity, and reduce production costs. This study aims to analyze the implementation of agricultural technology at PT Buyung Putra Perkasa in Pemulutan District, Ogan Ilir Regency. Using GR. Terry's implementation theory serves as an analytical framework that focuses on the four main components of implementation: determining, grouping, achieving goals, and assignments. This research uses a qualitative approach with a case study method. Data were obtained through interviews, direct observation, and documentation, then analyzed descriptively. The results showed that PT Buyung Putra Perkasa is a company engaged in rice field agriculture with an area of ± 300 hectares and has developed progress by using sophisticated technological tools in the process of work, thereby increasing rice productivity and running quite effectively from the aspects of company policies that support modern agricultural innovation, the competence of human resources as implementers, and supportive environmental conditions, both in terms of social, economic, and natural. The application of the technology used by PT Buyung Putra Perkasa has resulted in an increase in harvests from one two to three times each year.